1982
DOI: 10.1126/science.7089575
|View full text |Cite
|
Sign up to set email alerts
|

Cysteamine: a Potent and Specific Depletor of Pituitary Prolactin

Abstract: Cysteamine rapidly reduces the concentration of prolactin in pituitary tissue in vivo and in vitro. The effect is dose-dependent, reversible, and cannot be accounted for by prolactin release. Cysteamine does not appear to exert its effect through dopamine receptors and does not alter lactotrope morphology, as determined by electron microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
26
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 21 publications
9
26
0
Order By: Relevance
“…The plasma G H concentration was found to be markedly depressed in the rats with ARC lesions in the present study, similar to that found in rats with electrical or chemical lesions of the ARC in previous reports (1 5,19). CSH is known to be a depletor of SRIF and its reduction of SRIF levels in the hypothalamus is dose-dependent (16,20,21 (22,23). Indeed, serum levels of free T, were found to be decreased in the CSH-treated rats with ARC lesions.…”
Section: Discussionsupporting
confidence: 79%
“…The plasma G H concentration was found to be markedly depressed in the rats with ARC lesions in the present study, similar to that found in rats with electrical or chemical lesions of the ARC in previous reports (1 5,19). CSH is known to be a depletor of SRIF and its reduction of SRIF levels in the hypothalamus is dose-dependent (16,20,21 (22,23). Indeed, serum levels of free T, were found to be decreased in the CSH-treated rats with ARC lesions.…”
Section: Discussionsupporting
confidence: 79%
“…Cys teamine is a sulfhydryl drug which causes a rapid, revers ible and dose-dependent depletion of both pituitary and serum PRL levels [32], It does not act through interacting with DA receptors or increasing intracellular digestive processes of PRL [32]. Instead, it may disrupt the disul fide bridges within the PRL molecule and reduce the immunoreactivity of PRL [33].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, either pantothenate or cysteamine could be responsible for pantethine's hypolipemic action. Cysteamine has numerous pharmacologic actions (21) and hormonal effects (47,48). Pantothenate deficiency has been reported to lower blood cholesterol levels in the rat (49) and dog (50), but this was not demonstrated in humans (51).…”
Section: Discussionmentioning
confidence: 99%